Responsiveness of the mini-balance evaluation systems test, dynamic gait index, Berg balance scale, and performance-oriented mobility assessment in parkinson’s disease - Maryam Mehdizadeh; Seyed-Mohammad Fereshtehnejad; Merrill R. Landers; Parvaneh Taghavi Azar Sharabiani; Mohsen Shati; Seyede Salehe Mortazavi; Sayed Amir Hasan Habibi; Korosh Mansoori; Mahsa Meimandi; Zahra Nodehi; Zakieh Sadat Saberi; Ghorban Taghizadeh (Scientific Reports)
Abstract Commonly used clinical tools like the Mini-Balance Evaluation Systems Test (Mini-BESTest), Dynamic Gait Index (DGI), Berg Balance Scale (BBS), and Performance-Oriented Mobility Assessment (POMA) are essential for assessing balance impairments in people with Parkinson’s disease (PwPD), but their clinical relevance depends on understanding the Minimal Important Difference (MID) and Minimal Detectable Change (MDC). To assess the responsiveness of the Mini-BESTest, DGI, BBS, and POMA in PwPD. This prospective cohort study included 130 PwPD who were recruited. Participants underwent baseline and post-intervention assessments using the Mini-BESTest, DGI, BBS, and POMA. The intervention consisted of task-oriented exercises focused on motor re-learning to improve functional balance. Anchor and distribution methods were used to determine the MID (the receiver-operating characteristic(ROC)-based (MIDROC), the predictive modeling method (MIDpred), and the MIDpred-based method adjusted by the rate of improvement (MIDadj)) and MDC. ROC-derived MID(MIDROC) exceeded 1 point for all scales, but improvement-rate-adjusted MID (MIDadj) provided more conservative estimates: Mini-BESTest (2.96 points), DGI (2.29), BBS (1.97), and POMA (0.83). Predictive modeling (MIDpred) yielded higher thresholds (e.g., 4.0 for Mini-BESTest), likely reflecting baseline variability. The MDCs was 1.9, 2.0, 1.0, and 2.8 points for the Mini-BESTest, DGI, BBS, and POMA, respectively. The findings suggest that the Mini-BESTest, DGI, BBS, and POMA are responsive outcome measures for PD. This study’s results can provide valuable insights into interpreting changes in patient performance, thereby supporting clinical interventions and facilitating research planning.